PENGUJIAN PAPARAN RADIASI SINAR-X DI UNIT RADIOLOGI RSUD KOTA MAKASSAR - Yuliamdani, Riska; Sahara, Sahara; Fuadi, Nurul (JFT : Jurnal Fisika dan Terapannya, 2020)
The research has been conducted to determine the effect of exposure to a dose of radiation to the distance and time from the source of radiation and to determine how large exposure to radiation scattering which is received by a worker or operator in the space radiology Hospital Makassar. This research uses X-ray aircraft, Surveymeter, meter, and phantom. In measurements carried out two stages namely stage first measure exposure dose of radiation to the distance the results of the research that is done on testing the safety of exposure to radiation rays -X in units of radiology Hospital cities of Makassar, then obtained a conclusion as follows based on parameters of distance and time from the source of radiation effect large against Â dose of radiation exposure. A more far distance from the source of radiation the dose that is received by increasingly smaller. While the influence of the amount of time of the exposure beam of radiation that is increasingly long time irradiation then getting big too doses of radiation are obtained. Value exposure to radiation scattering which is received by the worker radiation chamber radiology Hospital of Makassar is the dose of radiation that is received by workers with long time use of radiation were the biggest received by operators XIII which amounted to 0.1769 mSv/h, while the value of the dose which is the smallest Â received by the operator XI of 0.0593 mSv/h and the average dose received by the operator is 0.1570mSv/h.